STUDY OF MODERN CRUSTAL DEFORMATIONS NEAR LARGE WATER RESERVOIRS IN SOUTHERN SIBERIA BY WATER LEVEL RECORDING - Timofeev V.Yu.; Arnautov G.P.; Taliev S.D.; Sarycheva Yu.K.; Kalish E.N.; Stus Yu.F.; Anisimova L.V.; Zhdanov A.A. (My University, 1997)
After describing the water level recording method for the study of modern crustal movements, the results are presented for different regions of south of Siberia: at Baikal rift - southwestern Baikal and Irkutsk power station reservoir; at Altai region: Teletskoe Lake; at south of West Siberia: Novosibirsk power station reservoir. Original results for vertical movements of faults and different parts of the Earth's crust are presented for subsidences in zones of large water reservoirs. Velocities are in accordance with geodetic and gravitational data. The subsidence of southern Baikal is estimated at 3-7 mm per year. Periodical movements of Teletskoe Lake region (7=7 years) are documented in the Altai region. Possibly, the rate of subsidence of the bottom of the Novosibirsk power station reservoir indicates that the effective viscosity of the upper mantle in this region is about 10e19-10e20 Pa∙s.
Keywords: VARIATIONS IN WATER LEVEL; MODEM CRUSTAL MOVEMENTS; SUBSIDENCE OF THE EARTH'S CRUST; EFFECTIVE VISCOSITY OF UPPER MANTLE; 525.622